PENGARUH COUNTRY OF ORIGIN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN MELALUI BRAND IMAGE TERHADAP PRODUK SOMETHINC DI KOTA SEMARANG - Izza Awlya Putri; Adhitya Yoga Prasetya (JURNAL ILMIAH EDUNOMIKA, 2025)
This research aims to examine the influence of Country of Origin and Product Quality on Purchase Decision, with Brand Image as a mediating variabel of Somethinc beauty product. In this research, purchase decision is defined as the dependent variable with country of origin and product quality identified as the independent variables. Brand image also function as intervening variable in this research. This research adopts a quantitative approach, using accidental sampling to collect data from 100 respondents who are users of Somethinc beauty product. Data analysis was conducted using Structural Equation Modeling (SEM) utilizing the SmartPLS 4 software. The results of this research show that Country of Origin, Product Quality and Brand Image have a positive and significant effect on Purchase Decision of Somethic beauty product.. Another result of this research is Brand image effectively mediates the relationship between country of origin and product quality on purchase decision of Somethinc beauty product.